2022
DOI: 10.1037/men0000369
|View full text |Cite
|
Sign up to set email alerts
|

Victims of virility: Honor endorsement, stigma, and men’s use of erectile dysfunction medication.

Abstract: The symptoms of erectile dysfunction (ED) pose a threat to physiological and psychological well-being, making it important that men feel comfortable seeking ED medication. Unfortunately, some men feel a sense of emasculation and shame in seeking medical help for their symptoms. The current research investigated how men in cultures of honor, who place strong emphasis on their masculine reputation and their virility, might be particularly hesitant to seek medication for ED symptoms due to the masculinity threat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 86 publications
(134 reference statements)
1
11
0
Order By: Relevance
“…Prior research has also shown that men may avoid screenings for fear of a positive test, as treatment for prostate cancer may lead to the loss or damage of their sexual function (James et al, 2017). Given that sexual virility is also an aspect of honor-endorsers’ masculine reputation (Brown, 2016; Foster et al, in press), these fears may need to be assuaged as well. It would likely be useful to use specific message-framing when practitioners present screening options to honor-endorsing patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has also shown that men may avoid screenings for fear of a positive test, as treatment for prostate cancer may lead to the loss or damage of their sexual function (James et al, 2017). Given that sexual virility is also an aspect of honor-endorsers’ masculine reputation (Brown, 2016; Foster et al, in press), these fears may need to be assuaged as well. It would likely be useful to use specific message-framing when practitioners present screening options to honor-endorsing patients.…”
Section: Discussionmentioning
confidence: 99%
“…Honor-state group classification divides the United States into honor and non-honor groups primarily by regional location. This division places most southern and western states in the honor-state category, with all other states (including Alaska and Hawaii) in the non-honor state category—this categorization established by Cohen (1998) has been used in a myriad of studies examining different outcomes as a function of regional differences in honor orientation (e.g., Barnes et al, 2012; Brown et al, 2009, 2014, 2018; Foster et al, in press; Osterman & Brown, 2011).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Another study analyzing reports of men being treated for prostate cancer, which often is accompanied by ED, revealed that the most important reasons why men feel a diminished sense of their masculinity are changes in bodily functions, such as the loss of the ability to achieve an erection, reduced libido, or impaired physical strength (Tsang et al, 2019). The fact that many men suffering from ED don't use ED medication has been shown to be associated with the emasculating stigma of ED help-seeking presenting a masculinity threat (Foster et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…3 ED patients have difficulty seeking medical support due to embarrassment and the condition is associated with psychological morbidities such as anxiety and depression. 4,5 ED may distress not just patients but their sexual partners, contributing to relational strain and reducing the quality of life for both. 6 First line treatment for ED includes phosphodiesterase-5 inhibitors (eg, Viagra, Cialis, Levitra), while second-line treatments include vacuum erection devices (VED) and intracavernous injections (ICI).…”
Section: Introductionmentioning
confidence: 99%